Nursing care and cultural diversity: a case study in a Primary Health Care Center in Murcia - Carmen Martínez Cano; Salvador Cayuela Sánchez (Universidad de Alicante, 2018)
Objective: The purpose of this study is to analyze and interpret how a group of nurses working at a Primary Health Care Center perceives cultural diversity. This involves describing their relationship with migrants, taking into account the attitude they have and the strategies they employ when attending these patients. Methodology: Qualitative design through semi-structured interviews developed in a Primary Health Care Center in Murcia (Spain). Analysis was carried out through coding, saturation and triangulation of the interviews, with the support of the data analysis software MaxQda® Results: This group of nurses associate cultural diversity with economic migrants, and label them in different ways. Their attitude in this respect strives to give equal health care to every patient. However, the language and cultural barrier they face on a daily basis makes them disagree on the clinical practice, so they suggest strategies to overcome this issue. Final thoughts: The presence of patients from diverse cultures in health care and the importance of providing culturally consistent care are obvious facts. Language and cultural barriers, as well as social prejudices and stereotypes, represent a barrier to establish a therapeutic relationship and practice Health Education.